Pertumbuhan Nafkah Ekowisata dan Kearifan Lokal yang Dilestarikan oleh Masyarakat Tengger di Desa Gubugklakah: Bagaimana Agar Berkelanjutan? - Hanim , Faridha; Hidayat , Kliwon; Kustanti , Asihing (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2023)
Integration between the needs for natural tourism exploration by urban communities has the potential to diversify agricultural and tourism livelihoods in rural communities. This phenomenon has triggered ecotourism growth through capacity development balanced with local wisdom preserved by the Tengger community in Gubugklakah Village. This study aims to: 1) Analyze the livelihood based on ecotourism growth by the farmers' community in Gubugklakah Village and 2) Explore the capacity development and local wisdom preserved by the Tengger community as ecotourism actors in Gubugklakah Village. This study used a qualitative approach with a descriptive research type. This study is located in Gubugklalah Village, which offers an ecotourism destination in Malang Regency with the attractiveness of local wisdom by the Tengger community. This study started from April to May 2021 and continued in September 2022 and March 2023. Data analysis used an interactive model by Miles and Huberman. The result shows that ecotourism growth in Gubugklakah Village includes agrotourism (apple-picking and agricultural cultivation education) and tourism forests (Lawangsari Café and Lodji Coffee Shop). Ecotourism management involves the local community through capacity development and local wisdom preservation, consisting of the traditional ceremony system, language, and livelihood system of the Tengger community in Gubugklakah Village.